Pressure-induced structural changes in α-MoO3 probed by X-ray absorption spectroscopy - Jonane, Inga; Anspoks, Andris; Nataf, Lucie; Baudelet, Francois; Irifune, Tetsuo; Kuzmin, Alexei (Institute of Physics Publishing, 2019)
Energy-dispersive X-ray absorption spectroscopy at the Mo K-edge was used to study pressure-induced (up to 36 GPa) changes in the local atomic structure of 2D layered oxide α-MoO3. A linear combination analysis based on the low and high-pressure X-ray absorption near edge structure (XANES) spectra shows clear evidence of two high-pressure phases, existing at 18-25 GPa and above 32 GPa. The first transition is due to gradual decrease of the interlayer gap, whereas the second one - to its collapse and oxide structure reconstruction. The local atomic structure around molybdenum atoms at 0.2, 18.5 and 35.6 GPa was determined from the extended X-ray absorption fine structure (EXAFS) using reverse Monte Carlo calculations.
The authors are grateful to Prof. Alain Polian for providing NDAC cell. The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020. The work was supported by philanthropist MikroTik and administrated by the University of Latvia Foundation.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics